Modeling the Consequences of Methane Gas Expansion in a CNG Fuel Stations of Isfahan Province - Mahdieh Rastimehr; Mahshid Bahrami; ali karimi; Reza Pourbabaki (بهداشت کار و ارتقای سلامت, 2021)
Abstract Introduction: Assessment of the consequences of hazards such as fire and explosion is one of the most urgent and important steps to improve the level of safety in the current stations and those that are in the design process. The purpose of this study was to review the model of CNG Compressed Natural Gas releases and the range of damages to individuals and equipment. Moreover, we examined the observance of  safe distance of this station to its surroundings. Materials and Methods: In this study, modeling the effects of fire and explosion on the CNG fuel station in Isfahan province was performed using ALOHA software. In this model, six scenarios were designed to create a hole with a diameter of 0.03m and a gap of 0.2m and width of 0.2 m in a pressure vessel. Results: It was observed that the toxic atmosphere was within the distance of 55 meters at a concentration of 65000 ppm. In the case of a gap, the toxic vapor cloud range could increase to 66 meters. The flammable superpower range was 89meters for the hole but 107 meters for the gap. The thermal radiation from the jet fire to the distance of 25meters was 10 kw/sqm for the hole, but the thermal radiation was 10 kw/sqm for the gap to 35meters. Conclusion: The most dangerous scenario was the Jet Fire, which involved not only the  CNG station, but also the municipal parking area. Furthermore,  the thermal radiation produced by the gap was greater than the hole with regard to the involved range.